2003
DOI: 10.1002/jbm.a.20064
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural comparison of hydroxyapatite and silicon‐substituted hydroxyapatite for biomedical applications

Abstract: Silicon-substituted hydroxyapatite (Si-HA) has been shown to lead to significantly increased rates of bone apposition when compared with phase-pure hydroxyapatite (HA) bioceramic implants (Patel N, et al. J Mater Sci Mater Med 2002;13:1199 -1206. However, uncertainty remains about the mechanism by which Si increases the in vivo bioactivity. In this study, defect structures in Si-HA were observed and characterized for the first time using highresolution transmission electron microscopy. Using tilting experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 23 publications
(32 reference statements)
3
67
0
1
Order By: Relevance
“…[13][14][15][16][17] Several opinions exist regarding the effect of silicon on the biological activity of HA-Si. [16,[19][20][21][22] The partial substitution of phosphate ions by silicate ions is accompanied by a significant deformation of the unit cell, which causes an increase in the dissolution rate of the apatite in the body fluid, its reactivity, and, as a consequence, its biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Several opinions exist regarding the effect of silicon on the biological activity of HA-Si. [16,[19][20][21][22] The partial substitution of phosphate ions by silicate ions is accompanied by a significant deformation of the unit cell, which causes an increase in the dissolution rate of the apatite in the body fluid, its reactivity, and, as a consequence, its biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…[10] A number of articles have been devoted to investigations of the partial silicate substitution of the phosphate group in the HA structure and its influence on the physical, chemical, and biological properties of the modified HA. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] In vitro and in vivo studies on cell cultures of animals and humans showed a more rapid formation of bone tissue cells on silicate-sub-high-resolution electron microscopy. The mechanochemical synthesis conducted in air is accompanied by the incorporation of carbonate ions into the apatite lattice, which results in the formation of B-type carbonated hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…28 The favourable effects of Si substitution in HA on bone cells have been related to passive and active mechanisms as material solubility increase, topographical changes, grain size reduction, surface charge modifications and ionic release of Si and Ca. [29][30][31][32][33] On the other hand, nanocrystalline hydroxyapatites (nano-HA) display enhanced bioreactivity in vivo with respect to HA, showing beneficial effects in the early stages of bone formation. 34,35 In order to know the angiogenic potential of VEGF-121 (2,5 µg) adsorbed on disks of crystalline and nanocrystalline hydroxyapatites with different Si proportion (nominal formula Ca 10 (PO 4 ) 6-x (SiO 4 ) x (OH) 2-x with x = 0, 0.25 and 0.40), EPCs were cultured on nano-HA, nano-SiHA 0.25, nano-SiHA 0.4, HA, SiHA 0.25, and SiHA 0.4 disks with or without immobilized VEGF-121.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Si-substituted HAp (Si-HAp) ceramics have a higher bioactivity as compared to pure HAp ceramics [5]. For example, substitution of a minute amount of Si into the HAp lattice has shown to improve dramatically the rate of bone-bonding ability with the implant materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ; HAp) is one of the main inorganic components found in the biological hard tissue, and it has the ability to bond directly with host tissue. Thus, HAp is considered as a material which is suitable for use in the biomedical applications, such as bone grafts and scaffolds for bone tissue engineering [1][2][3].…”
Section: Introductionmentioning
confidence: 99%